Changes in antidiabetic prescription patterns and indicators of diabetic control among 200, 000 patients over 13 years at a single institution in Japan. Issue 1 (December 2016) - Fujibayashi, Kazutoshi; Hayashi, Michio; Yokokawa, Hirohide; Naito, Toshio
Abstract Background We examined the long-term changes in the management of diabetes at a single institution in Japan. Methods Two repeated cross-sectional studies and a retrospective cohort study were conducted among patients who visited our institution between 2001 and 2013. We examined the changes in glycated hemoglobin (HbA1c) and glycated albumin levels, the prescription frequencies, and the daily doses of each antidiabetic agent among patients treated regularly for diabetes during the 13-year study period. The trends in control and treatment parameters were analyzed using Spearman's rank correlation coefficient. Results In the first repeated cross-sectional studies, 200, 298 patients had their glucose metabolism indicators measured, and diabetologists prescribed medications to 193, 445 patients. Of these, 170 patients were included in the retrospective cohort study. The patients' diabetic control tended to improve over the study period. The mean HbA1c level improved from 7.9 to 7.6% (from 63 to 60 mmol/mol) (rs = −0.11, p < 0.01) in the cross-sectional study, corresponding to a change from 8.2 to 7.7% (from 66 to 61 mmol/mol) (rs = −0.22, p < 0.01) in the retrospective study. The mean GA level improved from 22.7 to 20.7% (rs = −0.13, p < 0.01) in the cross-sectional study and from 23.5 to 21.5% (rs = −0.14, p < 0.01) in the retrospective study. Over the study period, prescription frequencies and daily doses of antidiabetic agents changed as treatment guidelines were altered. Conclusions The present study revealed a tendency toward long-term improvements in diabetic control, with changes in the prescription patterns consistent with research and guideline evidence.